Delimiting the Prospect of Openness: An Examination of Initial Student Approaches to E-Learning - Naughton, Christopher; Roder, John; Smeed, Juliette (International Review of Research in Open and Distributed Learning, 2011)
When converting from a paper-based distance mode to an online mode of teaching, certain expectations arise that students may engage not only in the development of extended research activity but that the quality of discussion and thinking will change. With access to open-ended discussion within the online forum the opportunity is afforded to students to share ideas and in turn develop their shared knowledge, a facility denied to them when in the paper distance mode. However, in a recent study conducted in New Zealand, it was shown that despite having access to online forums students moving to an online platform refrained from participation in this social exchange. A possible explanation for this indifference was thought to be the students realising that the online exchange made no impact on their assessment. Hence, the collaborative rhetoric of Web 2.0 made little impact when the summative evaluation remained unchanged from previous paper-based assessment. This paper reports on the introduction of online learning at a private tertiary college in New Zealand and describes the response of students who found difficulty in reconciling a community of learners and openness within what was perceived as an evaluation that remained individualistic and competitive in nature.